2015
DOI: 10.1167/iovs.15-16431
|View full text |Cite
|
Sign up to set email alerts
|

The Project MACULA Retinal Pigment Epithelium Grading System for Histology and Optical Coherence Tomography in Age-Related Macular Degeneration

Abstract: Retinal pigment epithelium morphology indicates multiple pathways in GA and CNV. Atrophic/scarred areas have numerous cells capable of transcribing genes and generating imaging signals. Shed granule aggregates, possibly apoptotic, are visible in SDOCT, as are 'Dissociated' and 'Sloughed' cells. The significance of RPE phenotypes is addressable in longitudinal, high-resolution imaging in clinic populations. Data can motivate future molecular phenotyping studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
183
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(199 citation statements)
references
References 139 publications
8
183
1
2
Order By: Relevance
“…We observed that the areas with the greatest photoreceptor disorganization were often associated with multilayered or atrophied RPE ( Fig. 1 F and H), histological abnormalities that are also hallmarks of human dry AMD (26). HG retinas showed multiple additional AMDf, including subretinal deposits and RPE vacuolation, hypopigmentation, thinning, and disorganization ( Figs Hallmarks of younger, healthy RPE were similar and more frequent in LG and HGxoLG RPE, including well-maintained basal infoldings with aligned mitochondria and typical numbers of pigment granules ( Fig.…”
Section: Resultsmentioning
confidence: 76%
“…We observed that the areas with the greatest photoreceptor disorganization were often associated with multilayered or atrophied RPE ( Fig. 1 F and H), histological abnormalities that are also hallmarks of human dry AMD (26). HG retinas showed multiple additional AMDf, including subretinal deposits and RPE vacuolation, hypopigmentation, thinning, and disorganization ( Figs Hallmarks of younger, healthy RPE were similar and more frequent in LG and HGxoLG RPE, including well-maintained basal infoldings with aligned mitochondria and typical numbers of pigment granules ( Fig.…”
Section: Resultsmentioning
confidence: 76%
“…As they occur in regions of GA, where no RPE is expected, it has been suggested that the hyperrelective material is not derived from lipofuscin or retinoid components. Recent work however has questioned if regions of GA really represent cell deserts, as patchy preservation of both the RPE and neurosensory retina has been observed (Zanzottera et al, 2015).…”
mentioning
confidence: 99%
“…The two fitted lines show similar slopes with a mutual difference of less than 5%, which proves the consistency of the PAM imaging and segmentation algorithm. Since the RPE cell suffers from morphology changes and melanosomes leaking at the early state of the diseases such as AMD [5] , the calculated distributions of cell area, intensity, and their correlation can be promising indicators for detecting cell abnormality caused by diseases.…”
Section: (D) and 4(h)mentioning
confidence: 99%
“…To achieve the cellular or subcellular imaging level, PAM systems have been developed to achieve micrometer or submicrometer resolution and used for imaging red blood cells and pigment cells [7,14,15] . Since the photoacoustic (PA) signals of RPE are mostly generated from the strong light absorption of the pigment components, especially the melanin, the PAM can display the cell morphology, and more importantly, indicate the melanin content in cells [16] , which is highly correlated with aging and retinal diseases such as age-related macular degeneration (AMD) [5,17] . To acquire the RPE cell features such as morphology and component content, accurate cell detection and segmentation in cellular images are important.…”
mentioning
confidence: 99%
See 1 more Smart Citation